Challenging The Primacy Of Lectures:The Dissonance Between Theory And Practice In University Teaching - Phillips, R. (Journal of University Teaching and Learning Practice, 2005)
Current practice in universities foregrounds the traditionallecture, tutorial, examination approach to teaching. Thenature of currently-accepted practice in course designand administration is considered through an examinationof the influence on universities of historical views aboutknowledge. These findings are contrasted with currentresearch about learning and learning environments, andthe dissonances explored in terms of the concepts oftheory-in-use and espoused theory. Recommendationsare then made about appropriate ways to designeducationally-sound learning environments in highereducation. Finally, this paper questions why lectures arelargely viewed as the core of the learning process, andwhy university teaching and learning practices continueto be resistant to, and often inconsistent with,fundamental principles of learning developed throughsustained scholarly enquiry.